Предмет: Алгебра,
автор: Unicorn717
СРОЧНО! ПОМОГИТЕ РЕШИТЬ ПОЖАЛУЙСТА,дам 17 баллов
Приложения:
![](https://files.topotvet.com/i/ecc/ecc5d5ea37f1964f854512b924d1bb11.jpg)
Unicorn717:
А можно решение,пожалуйста?
Ответы
Автор ответа:
0
1) разкроем дужки х/(3(х-3))-3/(х(х+3))+(х²+9)/(3(9-х²))=(3(х-3))-3/(х(х+3))+(х²+9)/(3(-(-х-3))(х+3))=(3(х-3))-3/(х(х+3))+
-(х²+9)/(3(х-3))(х+3))=(х²(х+3)-9(х-3)-х(х²+9))/(3х(х-3)(х+3))=(х³+3х²-9х+27-х³-9х)/(3х(х-3)(х+3))=(3х²-18х+27)/(3х(х-3)(х+3))=(3(х²-6х+9))/(3х(х-3)(х+3))=(х-3)²/(3х(х-3)(х+3))=(х-3)/(х(х+3))=(х-3)/(х²+3х)
2)выполним деление (х-3)/(4(х²+6х+9))×(х²+3х)/(х-3)=1/(4(х+3)²)/(х(х+3))=1/(4(х+3))×х=х/(4х+12)
3)выполним умножение
х/(2(2х+6))×(2х+6)=х/2
Ответ:х/2
-(х²+9)/(3(х-3))(х+3))=(х²(х+3)-9(х-3)-х(х²+9))/(3х(х-3)(х+3))=(х³+3х²-9х+27-х³-9х)/(3х(х-3)(х+3))=(3х²-18х+27)/(3х(х-3)(х+3))=(3(х²-6х+9))/(3х(х-3)(х+3))=(х-3)²/(3х(х-3)(х+3))=(х-3)/(х(х+3))=(х-3)/(х²+3х)
2)выполним деление (х-3)/(4(х²+6х+9))×(х²+3х)/(х-3)=1/(4(х+3)²)/(х(х+3))=1/(4(х+3))×х=х/(4х+12)
3)выполним умножение
х/(2(2х+6))×(2х+6)=х/2
Ответ:х/2
Автор ответа:
1
проверь еще сам(а) все................
Приложения:
![](https://files.topotvet.com/i/c51/c514a08c0affbd0c0afe85b2159c8ccb.jpg)
Похожие вопросы
Предмет: Математика,
автор: laskotatana862
Предмет: Литература,
автор: VasyaKopSUS
Предмет: Геометрия,
автор: elaklysnikova063
Предмет: Математика,
автор: Фло11
Предмет: Математика,
автор: абдул10